Práticas leitoras na era digital : suportes de leitura e o hipertexto - Nascimento, Maison Silva do (2016)
It is presented in this research, which is inserted in the field of History of Reading and the Book, the evolution of the reading supports. Starting from the relation reader-text-support, a revisit is made to the diverse manifestations of reading from the antiquity until the revolution of Gutenberg, being followed the presentation of the contributions of the appearance of the press until the decade of 1990, from which there is a survey of eletronic reading devices, which have caused profound changes in the publishing market and, consequently, in contemporary reading practices. To foster the theoretical grounding and the discussion of the theme, a dialogue between the authors Roger Fischer, Martyn Lyons, Alberto Manguel, and others is built. Keywords: reading, textual support, reading devices